2019
DOI: 10.1111/jocn.15015
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the nature of nursing care described by using the Caring Behaviours Inventory

Abstract: Aim To describe the nature of care received by patients measured through the Caring Behaviours Inventory. Background Professional nursing practice combines two dimensions of caring: instrumental care and expressive care. Instrumental care focuses on physical health needs, in terms of efficiency and employs interventions based on evidence. Expressive care is patient‐centred and based on the interpersonal relationship. It requires caring attitudes that include respect, kindness, sensitivity and patience. The Car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 43 publications
0
25
0
1
Order By: Relevance
“…The perception of patients differs from that of nurses; patients perceive a lower level of personal care than the one nurses believe that they deliver. Caring behaviors are affected by the working environment, nurses’ emotional intelligence and coping skills, and socio-demographic characteristics [ 2 ]. In fact, the perceived care in the nurse-patient relationship is high and instrumental in nature, and it can be stated that nurses consider that through their behaviors they transmit more care than the users perceive they receive [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The perception of patients differs from that of nurses; patients perceive a lower level of personal care than the one nurses believe that they deliver. Caring behaviors are affected by the working environment, nurses’ emotional intelligence and coping skills, and socio-demographic characteristics [ 2 ]. In fact, the perceived care in the nurse-patient relationship is high and instrumental in nature, and it can be stated that nurses consider that through their behaviors they transmit more care than the users perceive they receive [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Caring Behaviors Inventory scale (CBI) was developed based on Watson's theory [15]. It has been revised in several versions (43 and 42-item, 24-item, and 6-item) with excellent reliability (Cronbach's alpha 0.95-0.98) [16]. The various versions of this scale study the dimensions of "safety," "knowledge and skills," "respectful deference," "connectness," and "human presence" [16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been revised in several versions (43 and 42-item, 24-item, and 6-item) with excellent reliability (Cronbach's alpha 0.95-0.98) [16]. The various versions of this scale study the dimensions of "safety," "knowledge and skills," "respectful deference," "connectness," and "human presence" [16]. The CBI-24 has been validated in a sample of Cypriot and Greek nurses and patients [17].…”
Section: Introductionmentioning
confidence: 99%
“…32 Furthermore, nursing practice based on task-oriented care, where tasks are considered isolated duties, risks providing fragmented and non-person -centred care, fostering the depersonalization of caring. 33 The characteristics of the clinical learning environment could negatively influence students' learning in clinical setting. Nurse educators should encourage the creation of a positive learning environment that models and promotes caring through positive faculty and role modelling, since, as Labrague et al 12 suggested, instructors who teach caring positively influence nursing students' caring behavior.…”
Section: Introductionmentioning
confidence: 99%